AN ANALYSIS ON THE EFFECTIVENESS OF HAND PUPPET MEDIA TO FOSTER STUDENTS’ ABILITY IN TELLING THEIR EXPERIENCES - Kawengian, Kristy Presentya; Polii, Intama Jemy; Sepang, Elvie A. (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
Hand puppet is one of learning media which can be used to teach language skills, especially speaking, in classroom. The purpose of the study is to analyze the effectiveness of hand puppet media to improve 7th grade students’ ability in telling their experiences. This analytic descriptive study is conducted at SMP Negeri 6 Wosia, Tobelo Barat on June to August 2023. 20 7th grade students were the object of this study. The data collection is carried out using test, observation and documentation. The obtained data are analyzed descriptively. The findings show that the use of hand puppet media can improve students’ ability in telling their experiences effectively. Students’ learning outcomes become better as indicated by the improvement in their score. 75% of the 20 students involved managed to complete the assignment well. However, as many as 25% of students have not yet fully mastered the use of hand puppets in telling their experiences. The use of hand puppet media gives positive impact on the students as their participation during the learning process increases.